Organochlorine Pesticide Levels and Risk of Parkinson's Disease in North Indian Population. (8th July 2013) - Chhillar, Neelam; Singh, Neeraj Kumar; Banerjee, B. D.; Bala, Kiran; Mustafa, Md; Sharma, Deepika; Chhillar, Mitrabasu
Abstract : The cause of Parkinson's disease (PD) remains elusive, but environmental chemical exposures have been postulated to be involved in the etiology of PD. We examined the association between the persistent organochlorine pesticides (OCPs) and PD in the North Indian population. This case control study included 70 PD and 75 control subjects in the age group of 50 to 85 years. Blood samples were collected and high-purity grade hexane and acetone (2 : 1 ratio) were used for extraction of organochlorine residues. OCPs (hexachlorocyclohexane (HCH), aldrin, dieldrin, endosulfan, pp′-Dichlorodiphenyldichloroethylene (pp′-DDE), op′-DDE, pp′- Dichlorodiphenyltrichloroethane (pp′-DDT), op′-DDT, pp′-dichlorodiphenyldichloroethane (pp′-DDD) and op′-DDD) were quantitatively estimated by using gas chromatography. The most frequently detected OCP was dieldrin, which was present in 9.3% of control and 61.4% of PD. The strongest predictor was β -hexachlorocyclohexane (β -HCH), which reported an odds ratio of 2.566, indicating that for every additional one unit of β -HCH, patients had 2.566 times more chances of presence of PD. This study indicates that increased level of β -HCH and dieldrin may be associated with the risk of PD.